Silica-based planar lightwave circuits with high resistance against blue light for visible-light application. (1st August 2022) - Fujiwara, Yuji; Sakamoto, Junji; Katayose, Satomi; Hashimoto, Toshikazu; Watanabe, Kei
Abstract: We propose two novel types of waveguide, Zr-doped and non-doped silica, for high-power visible-light applications. We fabricated these waveguides and investigated their resistance against blue light. Both Zr-doped and non-doped silica waveguides showed one order of magnitude higher resistance against blue light compared with conventional Ge-doped silica waveguides. A comparison of their resistances indicated that Zr-doped silica waveguides are useful against blue light powers up to about 20 mW and non-doped silica waveguides have more potential for higher resistance against blue light powers over 20 mW.